Reconstruction of garden and open spaces of Szent György Hospital, Fejér County: Possibilities in open-air rehabilitation - Varró, Dorottya Katalin (4D Journal of Landscape Architecture and Garden Art, 2011)
The Szent György Hospital, Fejér County is the second biggest generál hospital in Hungary. In Transdanubia it is the biggest public health institution. It is responsible fór problems in the shire and alsó in the region. The hospital offers the complete spectrum of the national medical supply. Its building stock was expanded several times from the age of 1897 when it was established, however, according to my investigation there has nőt been any plán fór the complex landscape architecture of the garden. The free area from the blocks and the necessary routes were diversified by trees and shrubs. The Szent György Hospital of Székes- fehérvár has a “Régiónál and Social Infra- structure Operational Program” compe- tition with the aim to develop the health supply, urgency supply and the hospital- infrastructure. The program helps the environmental-friendly planning on the base of the requirements of the envi- ronmental-economical sustainability. Moreover, it protects the idea of building more up-to-date blocks in the mentality of complex accessibility. Furthermore, there are plans fór extension, recon- struction, renovation and modernization of the old blocks. During the recon- structions and demolitions a significant surface becomes free within the territory of the hospital. The organization of these places is opportune.